A Study on the Accessibility in Shopping Malls for People with Disabilities (PWDS) in Malaysia - Bashiti, Alaa; Rahim, Asiah Abdul (International Journal of Natural Sciences Research, 2015)
The objective of the paper: firstly, to evaluate accessibility and usability in the facilities that used by people with disabilities (PwDs) in shopping malls. Secondly, to identify whether the facilities provided in according with the latest Malaysian standards (MS 1184:2014) Universal Design and Accessibility in the Built Environment-Code of Practice. The paper will discuss disability and accessibility issues, current accessibility system in Malaysia, Malaysian Standards and universal design implementation in built environment and the importance of shopping malls in accessibility for Malaysia. It is a part of on-going research on universal design implementation in shopping malls. Accessibility in the shopping mall for people with disabilities PwDS is vital in order to provide and promote security and independence. Thus, in the planning of shopping malls well as in the design process, special considerations should be applied to accommodate the needs of the PwDs. Both qualitative and quantitative methods will be applied, by using descriptive analysis, observation, questionnaire, access audit simulation, checklist and interview. Photographic documentation is also taken for further analysis of the current facilities condition. Three case studies have been selected to evaluate accessibility of the shopping malls for People with Disabilities PwDs which are IKEA in Damansara, Suria Kuala Lumpur convention Centre (KLCC) in Kuala Lumpur and Alamanda in Putrajaya. The expected findings to identify whether the facilities provided match the needs of the people with disabilities, this is further supported by using the Malaysian standard (MS 1184:2014) Universal Design and Accessibility in the Built Environment-Code of Practice that fits and matches the facilities provided for various types of People with Disabilities PwDs.